2002
DOI: 10.1074/jbc.m204499200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Regulation of Casein Kinase I Activity by Group I Metabotropic Glutamate Receptors

Abstract: Previously, we reported that (S)-3,5-dihydroxypenylglycine (DHPG), an agonist for group I metabotropic glutamate receptors (mGluRs), stimulates CK1 and Cdk5 kinase activities in neostriatal neurons, leading to enhanced phosphorylation, respectively, of Ser-137 and Thr-75 of DARPP-32 (dopamine and cAMP-regulated phosphoprotein, 32 kDa). We have now investigated the signaling pathway that leads from mGluRs to casein kinase 1 (CK1) activation. In mouse neostriatal slices, the effect of DHPG on phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 39 publications
2
72
1
1
Order By: Relevance
“…Interestingly, the effect of DHPG on DARPP-32 Thr-34 phosphorylation was not antagonized by inhibitors of PLC, CK1, or Cdk5, indicating that the effect of mGlu5 receptors on Thr-34 is not mediated through the activation of PLC͞CK1͞Cdk5 signaling. Together with our previous studies (17,18), the present results indicate that group I mGlu receptors activate both ERK and PLC͞CK1͞Cdk5 signaling pathways in neostriatal neurons, and that ERK and PLC͞CK1͞Cdk5 selectively regulate different sites of DARPP-32 phosphorylation.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, the effect of DHPG on DARPP-32 Thr-34 phosphorylation was not antagonized by inhibitors of PLC, CK1, or Cdk5, indicating that the effect of mGlu5 receptors on Thr-34 is not mediated through the activation of PLC͞CK1͞Cdk5 signaling. Together with our previous studies (17,18), the present results indicate that group I mGlu receptors activate both ERK and PLC͞CK1͞Cdk5 signaling pathways in neostriatal neurons, and that ERK and PLC͞CK1͞Cdk5 selectively regulate different sites of DARPP-32 phosphorylation.…”
Section: Discussionmentioning
confidence: 53%
“…We have recently reported that, by activating casein kinase 1 (CK1) in a PLC-dependent manner, group I mGlu receptors cause an increase in the phosphorylation of DARPP-32 at Ser-137 (17,18). Moreover, by activating cyclin-dependent kinase 5 (Cdk5), this activation of CK1 causes an increase in the phosphorylation of DARPP-32 at Thr-75 (17).…”
Section: Activation Of Intracellular Signaling By Mglu5 Receptors Invmentioning
confidence: 99%
“…Group I mGlu receptors activate PLC␤ and stimulate the generation of inositol trisphosphate, leading to an increase in intracellular Ca 2ϩ . The increased intracellular Ca 2ϩ activates PP-2B, causing dephosphorylation of inhibitory autophosphorylation sites of CK1 , which results in its activation (11). Cdk5 is subsequently activated by CK1 (10) by an unknown mechanism and stimulates the phosphorylation of DARPP-32 at Thr-75.…”
Section: Regulation Of Darpp-32 Thr-34 Phosphorylation By Glutamate Nmentioning
confidence: 99%
“…Activation of group I mGlu receptors also increases DARPP-32 phosphorylation at Thr-75 as well as Ser-130 [casein kinase-1 (CK1)-site] (10). Group I mGlu receptors stimulate phospholipase C (PLC) and CK1 (11), resulting in activation of Cdk5 by an unknown mechanism, leading to phosphorylation of Thr-75. However, the signal transduction pathways mediating the biological effects of glutamate per se have not received much attention.…”
mentioning
confidence: 99%
“…In mammals and vertebrates, there are seven CK1 genes coding for ␣, ␤, ␥1, ␥2, ␥3, ␦, and isoforms (14), and some of these genes generate several proteins through alternative splicing (15). The CK1 isoforms may have different functions; for instance, CK1 is involved in regulating circadian rhythm through phosphoration of period (per) proteins (16), and it has also been linked to the activity of group I metabotropic glutamate receptors (17). CK1␦ may be involved in neurodegenerative diseases (18).…”
Section: Ck1mentioning
confidence: 99%